Capital Dynamics and Sustainable Growth in Six ASEAN Nations: GMM Estimation in The Perspective of SDGs - Wafiyulloh Mubarrok; Fitra Prasapawidya Purna; Rahul Chauhan; Arina Fitrianingsih (JURNAL ILMU MANAJEMEN, 2026)
Sustainable economic development in Southeast Asia remains a central theme in regional policy debates, particularly regarding the efficiency of factor accumulation. This study empirically investigates the dynamic relationships among physical capital, human capital, the labor force, and economic growth across six ASEAN countries (Indonesia, Vietnam, the Philippines, Cambodia, Laos, and Myanmar). Using a Two-Step System Generalized Method of Moments (GMM) approach for the period 2017–2023, the study addresses potential endogeneity issues and captures the path-dependent nature of regional growth. Empirical results demonstrate a high degree of growth persistence, with the lagged GDP coefficient indicating a strong momentum effect. Physical capital is found to be the primary driver of economic expansion, validating the importance of sustained infrastructure investment. In contrast, human capital and labor force participation do not have a statistically significant impact on GDP, highlighting the profound "education-growth puzzle" and potential skills mismatch in the region. These findings suggest that, despite ASEAN's growth being underpinned by a capital-intensive strategy, the region faces structural challenges in translating human capital expansion into tangible productivity gains. Policy recommendations emphasize the need to shift from quantity-based to quality-based education, as well as to better align academic curricula with industry demand, to ensure inclusive, productivity-based growth in line with SDGs 4, 8, and 9.